Jaws 2 / Jaws 3 / Jaws the Revenge (Universal City, CA : Universal Studios, 2015)
"Just when you thought it was safe to go back in the water ... all three sequels from one of the most successful blockbusters of all time are featured in the Jaws 3-Movie Collection. Years after being terrorized by a giant white shark, the vacationers on Amity Island begin disappearing again in an all-too-familiar fashion and seek the help of Police Chief Brody (Roy Schneider) in Jaws 3. In Jaws 3, tourists marvel at the new Undersea Kingdom, a maze of underwater glass tunnels that allow visitors to get up closer to marine life than ever before, until they get an unexpected visit from a very angry shark. Finally, in Jaws: The Revenge, Brody's wife seeks refuge in the Bahamas only to find herself reliving the horrors of the past and decides to take matters into her own hands. This time, it's personal."--Container.
Jaws 2 (117 min.) -- Jaws 3 (99 min.) -- Jaws: The Revenge (91 min.).
Bonus features: making of, deleted scenes, featurettes, theatrical trailers.
Jaws 2 -- Written by Carl Gottlieb and Howard Sackler ; directed by Jeannot Szwarc ; music by John Williams ; produced by Richard D. Zanuck and David Brown.
Jaws 3 -- Directed by Joe Alves ; produced by Rupert Hitzig.
Jaws: The Revenge -- Directed and produced by Joseph Sargent.
Jaws 2 -- Starring Roy Scheider, Lorraine Gary, Murray Hamilton.
Jaws 3 -- Starring Dennis Quaid, Bess Armstrong, Simon MacCorkindale, Louis Gossett Jr.
Keywords: Shark attacks -- Drama; Sharks -- Drama; DVDs; DVD-Video discs; Videodiscs; Action and adventure films; Drama; Feature films; Horror films; Thrillers (Motion pictures); Video recordings for the hearing impaired